Quality evaluation, consumer acceptability, and cost-benefit analysis of mango-plus beverage - Olufemi, Owolade Samuel; Ruth, Aderibigbe Olaide; Oluwakemi, Mustapha Balikis; Olufemi, Ademoyegun Temitope; Bosede, Adeoye Iyabo (International Journal of Sustainable Agricultural Research, 2024)
This study aims to produce a mango-plus beverage from a blend of mango and pineapple fruits and its market prospects determined. Mango and pineapple were processed into beverages at different ratios (1:0, 1:1, 1:2, and 1:3) and coded as FKJ, WTC, PMG, and QTC, respectively. Parameters that include proximate, TSS, pH, vitamin C, total phenol, sensory characteristics, microbial load, and cost-benefit analysis were determined. Findings show significant differences existed among the sample’s parameters at p<0.05. Sample QTC, which was a mango-pineapple blend (1:3), gave the highest ash content (1.64%), which was higher than FKJ (1.00%), WTC (1.43%), and PMG (1.46%). Similarly, QTC has the highest energy (54.27 kcal/100 mL), significantly higher than sample FKJ (30.95 kcal/100 mL), WTC (44.03 kcal/100 mL), and PMG (50.53 kcal/100 mL) at p<0.05. Vitamin C for samples was between 12.15 mg/100 mL and 13.33 mg/100 mL; total phenol was between 204.44 mg/100 mL and 249.50 mg/100 mL; and antioxidant activity ranged between 50.11 mg/100 mL and 60.68 mg/100 mL, respectively. QTC has the highest vitamin C concentration (13.33 mg/mL), significantly higher (p<0.05) than other samples. Additionally, QTC (1:3) has the highest phenol (249.50 mg/100 mL), significantly higher than FKJ (204.44 mg/100 mL), WTC (224.22 mg/100 mL), and PMG (244.22mg/100mL). The microbial loads (cfu/100 mL) were within an acceptable range, indicating their suitability for human consumption during the evaluation period. Cost-benefit analysis suggested prospects for favourable returns. The practical implication of the study is that mango-pineapple at a ratio of 1:2 and 1:3 has good market prospects.